PERAN PEMERINTAH DESA DALAM PENGEMBANGAN WISATA SAMALENGOH DI DESA GUNTURMEKAR KECAMATAN TANJUNGKERTA KABUPATEN SUMEDANG - Yuyun Sopiani Nurjanah (LPPM UNSAP, 2026)
The development of village tourism has become a crucial strategy in improving the welfare of local communities. This study aims to analyze the role of the Gunturmekar Village Government in the development of Samalengoh tourism, located in Tanjungkerta Subdistrict, Sumedang Regency. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The focus of the study includes the facilitative, educative, representational, and technical roles carried out by the village government. The findings indicate that the Gunturmekar Village Government plays a significant role in providing basic infrastructure, establishing and mentoring the Tourism Awareness Group (Pokdarwis), and conducting training for the community in tourism management. The government also contributes to tourism promotion and establishes external collaborations with various stakeholders. Challenges identified include budget limitations, suboptimal community participation, and difficulties in attracting investors. In conclusion, the village government's role in each of these dimensions greatly influences the success of Samalengoh tourism development. The implication of this research highlights the need to strengthen collaboration among the village government, local communities, and external partners. It recommends strategies to enhance community capacity and participation, as well as optimize budgetary support to ensure the sustainability of village tourism development.